PELATIHAN PEMERIKSAAN TAJAM PENGLIHATAN PADA SISWA KELAS 5 SD GEDONGAN I, COLOMADU, KARANGANYAR - Em Sutrisna; Dedi Hanwar; Peni Indrayudha; Tanti Azizah Sujono (Universitas Muhammadiyah Surakarta, 2007)
Seeing is crucial aspect in life includes in the field of education. Ifit is not cured the reduction of sharpness of seeing/visus can affect thestudent ability to study. This action is done to detect this reduction early.Therefore, the eyes will not be getting worse. The research is done bytraining and demonstrating how to check visus. The location of the researchis SD Gedongan I, Gedongan, Colomadu, Karanganayar. The 31 studentsare checked. The result is that there are 3 students have visus with miop.All the students can participate in this research well.